CYP2D6 polymorphisms in selected South African populations - Coetsee, Christa (University of the Free State, 2005)
Debrisoquine 4-hydroxylase, also known as CYP206, is a cytochrome P450 enzyme responsible for the metabolism of many commonly used drugs such as antispychotics, beta-blockers, opiates and tricyclic antidepressants. Polymorphic expression of CYP206 is observed in the interethnic and inter-individual variability in patients undergoing treatment with these drugs. Two distinct phenotypes have been described for this enzyme in Caucasian populations, namely extensive and poor metabolisers. The poor metaboliser phenotype behaves as an autosomal recessive trait occurring in about 7% of Caucasians. Major discordance has been observed when comparing Caucasian data with data from other ethnic groups. Accurate prediction of a patient's genotype could be important for many cl inically used drugs as poor metabolisers are at a high risk for adverse drug reactions, onset of toxicity and even therapeutic failure. Early or preventative therapy guided by genotyping could significantly enhance the clinical outcome for these patients. In this study we determined the frequency of CYP206 polymorphisms in three Southern African populations, namely Caucasian (control), Black and Coloureds. Our results for the Caucasian group largely confirm the findings of other studies in the sense that 96 % of subjects are extensive metabolisers (normal). However, based on their genotypes, only 67 % of Coloured and 69 % of Black subjects are predicted to be extensive metabolisers. A high prevalence of intermediate (IM) metabolisers was observed for both the Black (24 %) and Coloured (26 %) groups. CYP206*17 occurred at a high frequency in the Black (0.2324) and Coloured (0.1301) goups, while CYP206*10 also occurred at a high frequency in the Coloured (0.1301) group. Both these groups show reduced-activity alleles unique to them, not found in the Caucasian subjects. If confirmed by phenotyping subjects on a relevant treatment, these findings may have implications for treatment of patients with drugs metabolised by CYP206.

Debrisoquine 4-hidroksilase, oak bekend as CYP2D6, is 'n sitochroom P450 ensiem, verantwoordelik vir die metabolisme van baie algemeen gebruikte middels soos antipsigotika, beta-blokkers, opiate en trisikliese antidepressante. Die polimorfiese uitdrukking van CYP2D6 word in pasiente tydens behandeling waargeneem as interetniese en interindividuele variasie. Twee definitiewe fenotipes is vir hierdie ensiem beskryf in blanke populasies, nl. normale en swak metaboliseerders. Die swak metaboliseerder fenotipe is 'n autosomale resessiewe eienskap wat in omtrent 7 % blankes voorkom. Groot teenstrydighede is waargeneem wanneer blanke data met ander etniese groepe vergelyk word. Akkurate voorspelling van 'n pasient se genotipe kan baie belangrik wees vir 'n wye reeks geneesmiddels omdat swak metaboliseerders 'n hoe risiko vir nadelige geneesmiddel reaksies, ontwikkeling van toksisiteit en selfs die mislukking van terapie het. Die ondersteuning van vroee of voorkomende terapie deur genotipering kan die kliniese uitkoms van hierdie pasiente baie verhoog. In hierdie studie het ans die frekwensie van die CYP2D6 polimorfismes in drie Suid Afrikaanse populasies, naamlik Blank, Swart en Kleurling, bepaal. Die resultate vergelyk baie goed met die bevindings vir ander Blanke bevolkingsgroepe en 96 % van proefpersone het normaal getoets. Net 67 % Kleurlinge en 69 % Swartes is as normaal geklassifiseer na aanleiding van hul genotipes. Die voorkoms van intermediere metaboliseerders was baie hoog vir beide die Swart (24 %) en Kleurling (26 %) groepe. Ons het oak bevind dat CYP2D6*17 in 'n baie hoe frekwensie in die Swartes (0.2324) en Kleurlinge (0.1301) voor kom, terwyl CYP2D6*10 oak in Kleurlinge (0.1301) in 'n hoe frekwensie voorkom. In beide hierdie groepe is allele met verlaagde aktiwiteit gekry wat nie onder die Blankes voor kom nie. Bevestiging van hierdie resultate met fenotipering kan groat implikasies he vir pasiente op behandeling met geneesmiddels wat deur CYP2D6 gemetaboliseer word.
Thesis (Ph.D. (Haematology and Cell Biology))--University of the Free State, 2005
Keywords: Pharmacogenetics; Ethnicity; Genotyping; Sequencing; Drug metabolising enzymes; Cytochrome P-450; Drugs -- Design